Solar Irradiance Variability: Comparisons of Models and Measurements. Issue 12 (28th December 2019) - Coddington, O.; Lean, J.; Pilewskie, P.; Snow, M.; Richard, E.; Kopp, G.; Lindholm, C.; DeLand, M.; Marchenko, S.; Haberreiter, M.; Baranyi, T.
Abstract: The Earth system responds to solar variability on a wide range of timescales. Knowledge of total solar irradiance (TSI) and solar spectral irradiance (SSI) spanning minutes to centuries is needed by scientists studying a broad array of research applications. For these purposes, the NOAA National Centers for Environmental Information (NCEI) Climate Data Record Program established the Solar Irradiance Climate Data Record. Version 2 of the Naval Research Laboratory's solar variability models that are derived from and demonstrate consistency with irradiance observations specifies TSI and SSI for the Solar Irradiance Climate Data Record. We establish the veracity of the Naval Research Laboratory models on the timescales and over the wavelength range for which the Sun is known to vary and, thereby, specify the utility of these models. Through comparisons with irradiance observations and independent models, we validate NRLTSI2 estimates of TSI on solar rotational (~27‐day), solar cycle (~11‐year), and multidecadal (spacecraft era) variability timescales. Similarly, we validate NRLSSI2 estimates of SSI rotational variability in the ultraviolet through the mid‐visible spectrum. Validation of NRLSSI2 estimates at longer wavelengths, particularly in the near‐infrared, and for the full spectrum at solar cycle timescales and longer is not possible with the current observational record due to instrumental noise and instrument instability. We identify where key new data sets, such as observations from the Total and Spectral Solar Irradiance Sensor‐1, are expected to provide a fuller understanding of total and spectral solar irradiance variability on multiple timescales. Plain Language Summary: An understanding of total and spectral solar irradiance is essential for Earth atmospheric and climate studies because the Sun's energy incident at the top of Earth's atmosphere is the dominant energy source driving a myriad of interactions that establish Earth's climate. We describe how the National Oceanographic and Atmospheric Administration's Solar Irradiance Climate Data Record is meeting the goal to model variability in the Sun's irradiance, identify limitations in our current understanding of solar irradiance variability on multiple timescales and over a broad spectral range, and highlight where new observations are expected to provide a fuller understanding. Key Points: The Naval Research Laboratory's solar variability models, NRLTSI2 and NRLSSI2, establish the Solar Irradiance Climate Data Record (CDR) The CDR total and spectral (between 265 and 500 nm) solar rotational estimates are validated by observations on 27‐day solar rotations On solar cycle timescales and longer, particularly in the spectrum, differences in observational data sets preclude model validation